Seasonal patterns of energy allocation to basal metabolism, activity and production for livestock in a nomadic pastoral ecosystem - Coppock, D. Layne; Swift, D.M.; Ellis, J.E.; Galvin, K.A. (Cambridge University Press, 1986)
Presents energy budgets and estimates of forage intake requirements developed for adult camels, cattle, sheep and goats managed by nomads of the arid Turkana district of north - western Kenya. Includes data on livestock activity patterns, diet quality, weight changes and milk yields with literature based estimates of the associated costs and efficiencies